The Effect of Small Movement Games On Improving Some Referential Thinking Skills and Academic Achievement In Fifth Grade Science Class - AbdMajeed, Rana (Journal of Physical Education, 2016)
The importance of the study lies in thinking and the different methods used to improve it. The researcher used a teaching program including small games in physical education class to explain fifth grade primary school science. The researcher aimed t identifying the effects of these games on referential thinking and academic achievement. The problem of the research lies in difficulties faced by students in science class. The aim of the research was to identify the effect of small movement games in improving referential thinking and academic achievement in science class / primary school. The researcher hypothesized statistical differences between experimental and controlling groups in improving referential thinking and academic achievement in favor of the experimental group. The researcher used the experimental method. The results showed positive effect of small games in physical education class to improve referential thinking and academic achievement in science class. The researcher recommended the necessity of making a program for science class as well as other classes that concentrates on all thinking skills in general and referential thinking in particular.